Treatment of experimental colitis by endometrial regenerative cells through regulation of B lymphocytes in mice - Xu, Xiaoxi (Stem Cell Res Ther, 2018)
BACKGROUND: Endometrial regenerative cells (ERCs), a novel type of mesenchymal-like stem cell derived from menstrual blood, have been recently evaluated as an attractive candidate source in ulcerative colitis (UC); however, the mechanism is not fully understood. The present study was designed to investigate the effects of ERCs, especially on B-cell responses in UC. METHODS: In this study, colitis was induced by administering 3% dextran sodium sulfate (DSS) via free drinking water for 7 days to BALB/c mice. In the treated group, mice were injected intravenously with 1 × 10(6) ERCs on days 2, 5, and 8 after DSS induction. Therapeutic effects were assessed by monitoring body weight, disease activity, and pathological changes. Subpopulations of lymphocytes were determined by flow cytometry. IgG deposition in the colon was examined by immunohistochemistry staining. Cytokine levels were measured by enzyme-linked immunosorbent assay (ELISA), Western blot, or polymerase chain reaction (PCR) analysis. Adoptive transfer of regulatory B cells (Bregs) into colitis mice was performed. RESULTS: Here, we demonstrated that ERC treatment prolonged the survival of colitis mice and attenuated disease activity with fewer pathological changes in colon tissue. ERCs decreased the proportion of immature plasma cells in the spleen and IgG deposition in the colon. On the other hand, ERCs increased the production of Bregs and the interleukin (IL)-10 level. Additionally, adoptive transferred Bregs exhibited significant therapeutic effects on colitis mice. CONCLUSIONS: In conclusion, our results unravel the therapeutic role of ERCs on experimental colitis through regulating the B-lymphocyte responses.